System-level biological effects of extremely low-frequency electromagnetic fields: an in vivo experimental review - Tian, Haoyang; Zhu, Haozheng; Gao, Chenhao; Shi, Mingxia; Yang, Dekun; Jin, Mingyu; Wang, Fenghua; Sui, Xiaohong (Frontiers in Neuroscience, 2023)
During the past decades, potential effects of extremely low frequency electromagnetic fields (ELF-EMFs) on human health have obtained great interest all around the world. Though the International Commission on Non-Ionizing Radiation Protection recommended a 100 μT, and then 200 μT magnetic field limit, the long-term effects of ELF-EMFs on organisms and systems need to be further investigated. It was reported that both electrotherapy and possible effects on human health could be induced under ELF-EM radiation with varied EM frequency and fields. This present paper intends to systematically review the in vivo experimental outcome and the corresponding mechanisms to shed some light on the safety considerations of ELF-EMFs. This will further help advance the subsequent application of electrotherapy in human health.